What Type of Finance Matters for Growth? : Bayesian Model Averaging Evidence - Hasan, Iftekhar; Horvath, Roman; Mares, Jan (World Bank, Washington, DC, 2016)
This paper examines the effect of finance on long-term economic growth using Bayesian model averaging to address model uncertainty in cross-country growth regressions. The literature largely focuses on financial indicators that assess the financial depth of banks and stock markets. These indicators are examined jointly with newly developed indicators that assess the stability and efficiency of financial markets. Once the finance-growth regressions are subjected to model uncertainty,the results suggest that commonly used indicators of financial development are not robustly related to long-term growth. However, the findings from the global sample indicate that one newly developed indicator -- the efficiency of financial intermediaries -- is robustly related to long-term growth.